TEORI KEPEMIMPINAN SIFAT - Maria Merry Marianti (Center for Economic Studies Universitas Katolik Parahyangan, 2009)
Leadership is the ability to influence a group toward the achievement of a vision or a set of goals. There are three groups of Leadership theories: trait theories, behavioral theories, and contingency theories. Trait theories of leadership differentiate leaders from non-leaders by focusing on personal qualities and characteristics. This paper focuses on trait theories of leadership. This theory is based on characteristics of many leaders - both successful and unsuccessful - and is used to predict leadership effectiveness.